Synthesis of a Fe3O4/PAA-based magnetic fluid for faraday-rotation measurements - Kürçükdermenci, Serhat (Materiali in tehnologije, 2013)
Highly water-soluble Fesub{3}Osub4/PAA (polyacrylic acid) nanoparticles (NPs) were synthesized with the high-temperature hydrolysis method. We report the first demonstration of Faraday rotation (FR) for a magnetic fluid (MF) synthesized with this novel method. The experiments were performed in the DC regime (0-6 . 10sup{-2} T) at room temperature for 14 concentrations from 1.8 mg/ml to 5 mg/ml. The maximum rotation was recorded as 0.96° cmsup-1 for 3.33 mg/ml and this is called the critical concentration (CsubCRITICAL). It was found that the rotation tends to decrease when the concentration is higher than CsubCRITICAL. The MF behavior for FR is discussed with respect to substructure interactions (particle-particle, chain-chain). This work provides a new insight for the FR investigations of MFs including highly water-soluble magnetic NPs.
Keywords: magnetna tekočina; nanodelci; železov oksid; Faradeyeva rotacija